78.2k views
3 votes


y=−2x−4
y=3x+3


User Rob Burke
by
5.7k points

1 Answer

5 votes
Since there is no question I do not know what is being solved for, but if you’re wondering what the value of x and y equal here’s the explanation.

Set up both equations equal to each other > -2x-4 = 3x+3
Subtract 3 from both sides to get > -2x-7 =3x
Subtract the -2x on both sides to get > -7 = 5x.
Divide both sides by 5 and x = -1.40 or (-1 2/5)

In order to get y value take one of the equation and replace the x in the equation with the value of x you just solved for.
y = -2(-1.4) - 4
multiply the number in the parenthesis and the -2 and you get > y = 2.8 - 4
subtract the two and y = 1.2

x = -1.4 (-1 2/5)
y = 1.2 (1 1/5)

User Shazam
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.